Penerapan Metode Projected Unit Credit dan Entry Age Normal pada Asuransi Dana Pensiun - Bayu Nanda Permana; Yuki Purnamasari; Ika Purnamasari (EKSPONENSIAL, 2016)
Actuarial calculation method in pension funding is divided into two major categories, namely Accrued Benefit Cost Method and Projected Benefit Cost Method. One example method which is included in Accrued Benefit Cost Method is the Projected Unit Credit Method, and one of the method which is included in Projected Benefit Cost Method is the Entry Age Normal Method. Both methods are used to determine the amount of normal cost and actuarial liabilitiy which are the basis in determining pension benefits. The purpose of this study was to compare the value of normal cost and actuarial liabilities of the two methods. The data used in this research is the employee data from PT. INHUTANI I Berau Branch. The result showed that normal cost using Projected Unit Credit method continued increases with the salary received, meanwhile if using the Entry Age Normal method the amount of normal cost is same for each year to an employee. On the other hand, actuarial liability using Projected Unit Credit Method is smaller than using Entry Age Normal for each employee in each year.